Clinical utility of brain stimulation modalities following traumatic brain injury: current evidence - Li S (Dove Medical Press, 2015)
Shasha Li,1,2 Ana Luiza Zaninotto,2,3 Iuri Santana Neville,4 Wellingson Silva Paiva,4 Danuza Nunn,2 Felipe Fregni21Department of Rehabilitation Medicine, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Spaulding Neuromodulation Center, Harvard Medical School, Boston, MA, USA; 3Division of Psychology, Hospital das Clínicas, University of São Paulo, São Paulo, Brazil; 4Division of Neurosurgery, University of São Paulo Medical School, São Paulo, São Paulo, BrazilAbstract: Traumatic brain injury (TBI) remains the main cause of disability and a major public health problem worldwide. This review focuses on the neurophysiology of TBI, and the rationale and current state of evidence of clinical application of brain stimulation to promote TBI recovery, particularly on consciousness, cognitive function, motor impairments, and psychiatric conditions. We discuss the mechanisms of different brain stimulation techniques including major noninvasive and invasive stimulations. Thus far, most noninvasive brain stimulation interventions have been nontargeted and focused on the chronic phase of recovery after TBI. In the acute stages, there is limited available evidence of the efficacy and safety of brain stimulation to improve functional outcomes. Comparing the studies across different techniques, transcranial direct current stimulation is the intervention that currently has the higher number of properly designed clinical trials, though total number is still small. We recognize the need for larger studies with target neuroplasticity modulation to fully explore the benefits of brain stimulation to effect TBI recovery during different stages of recovery.Keywords: traumatic brain injury, brain stimulation, neuroplasticity